Campur Kode Dalam Podcast Denny Sumargo Dan Livy Renata - Chaeril Anam; Farikul Hasan; Muhammad Mufti Eka Prasetyo (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Language as a means of communication between humans is an object of discussion in linguistics, which is not a little influenced by the conditions and social developments of the community as its users. One of the phenomena that occurs is the occurrence of code mixing in a speech. This code mixing is caused by social conditions that do not only consist of one language, it is possible that each region has its own language. YouTube is one of the results of social development, where language can be found there. YouTube presents several types of content such as podcasts, or casual chats. One example is the famous YouTuber, Denny Sumargo who on one occasion invited Livy Renata as his guest star. From the podcast, several code mixing phenomena occurred, especially considering the background of their biodata as Indonesian citizens who both have Chinese blood, making it possible for both of them to not only master one language, so that in the podcast the code mixing phenomenon can be found.